Characterization and acidic properties of Al-SBA-3 mesoporous material - Anunziata, Oscar Alfredo (2010)
SBA-3 mesostructured silica containing framework aluminum is reported here. This material was successfully synthesized using sodium aluminate via post synthesis method. The structural properties of this novel material were studied by X-ray diffraction and FTIR. The Al insertion was determined by 27Al-NMR and the acidity was monitored by infrared spectroscopy of Pyridine adsorption/desorption. The 27Al NMR results indicate that Al has been effectively incorporated into the framework of SBA-3 material by post-synthesis method. The bridging hydroxyl (Si3O–Al–OH) acid sites are observed after the adsorption of basic probe molecules, such as pyridine; this fact strongly supports the presence of Bronsted acid sites. The alumination of Si-SBA-3 produces stronger Brønsted acidity than the conventional mesoporous aluminosilicates.